Haitekeu / Nur Nazlin Zahri and Muhammad Nizam Azhar - Zahri, Nur Nazlin; Azhar, Muhammad Nizam (Universiti Teknologi MARA, Kedah, 2018)
Portable speaker or wireless speakers are loudspeakers which receive audio signals using radio frequency waves rather than over audio cables . It's handy in size and easy to be carried. The design and a material used of a product is the main topic on these days and one of the causes is the design does not suit well with the user . The purpose of this study is to understand the principles , problems , and approaches of the user and the product . The objective of the research is to produce a new portable speaker that suited with trans hi tech criteria . The qualitative interview and role play interview was used to get primary data to gather the information . The research is focused on design and to solve the problems that based on the interview . The research have found out the opportunity of using new material in the product that become the major role in produce a portable speaker that influence by trans hi tech criteria .